Shipping strategies of listed shipping companies during peaks and troughs - Μπατσολάκης, Σπυρίδων (2017)
The aim of this study is to investigate the strategic profile of shipping companies during peak and trough periods. For that purpose, 12 shipping companies, listed on the International Stock Exchange System, have been selected; specifically four from every shipping sector, namely bulk, tanker and container. The strategies of these particular companies have been examined for the periods between 2005 and 2008 (peak period) and between 2009 and 2015 (trough period). The study uses two financial ratios and two shipping ratios in order to examine how these strategies affect companies’ performance. According to the findings companies appear to adapt their strategic profile during trough period. More specifically they focus on how to reduce operation costs and obtain stable cash flow. The findings also suggest that shipping companies during trough period continue to invest into new vessels, in order to have strategic advantage when the trough period ends.